The influence of selected parameters of spray cooling and thermal conductivity on heat transfer coefficient - Cebo-Rudnicka, Agnieszka; Malinowski, Zbigniew; Buczek, Andrzej (International journal of thermal sciences, 2016)
The influence of water spray pressure, water flux and the nozzle-to-surface distance on the heat transfer coefficient during spray cooling of brass and inconel samples has been investigated. The inverse method has been employed for the heat transfer coefficient identification. The objective function defines dimensionless deference between measured and calculated temperatures. The inverse solution starts with an assumption of a general form of an approximating function of the heat transfer coefficient distribution at the cooled surface as function of sample radius and time. The unknown parameters which define the heat transfer coefficients are determined by minimizing the objective function. The variable matrix method which utilizes the Broyden-Fletcher-Goldfarb-Shanno updating technique has been employed to minimize the objective function. Uncertainty of the inverse solution has been tested based on the assumed heat transfer coefficient distribution simulating nearly real spray cooling conditions. The numerical tests have indicated significant changes in the identified heat transfer coefficients depending on the quality of the heat conduction model. The experiments of spray cooling were conducted and the temperature was measured at the selected points in the cylindrical sample. The measured temperatures have been used as an input data for the heat transfer coefficient identification. The finite element model selected based upon numerical tests has been employed in computing the sample temperature field necessary for identifying the heat transfer boundary conditions. The objective function minimizations have given the heat transfer coefficients at the cooled surface as functions of time and surface temperature for brass and inconel samples. The influence of spray cooling parameters on the heat transfer coefficient has been discussed. •Uncertainty tests concerning the influence of the heat conduction model on the heat transfer coefficient identification.•Significant influence of metal conductivity on the identified heat transfer coefficients during spray cooling.•The heat transfer coefficient dependence on water flux and pressure as functions of surface temperature for selected metals.•The maximum of the heat transfer coefficient dependence on cooling parameters.•The initial temperature of the cooled sample influence on the heat transfer coefficient.